Prototipe Pendeteksi Keberadaan Pelanggan Pada Meja Restoran Berbasis Mikrokontroler dengan Notifikasi Telegram - Fatihaturrizkah; Werman Kasoep; Nefy Puteri Novani (Universitas Andalas, 2023)
The culinary business is the top two contributors from the manufacturing sector (6.66%). The Association of Indonesian Food and Beverage Entrepreneurs (GAPMMI) estimates that the food and beverage industry will grow by 7% by the end of 2022, this shows that the basic needs business such as the food or beverage business has good business prospects. A restaurant at certain hours such as lunch, dinner and on certain days, will be the busiest time to visit. It is at this time that the service of a restaurant will find it difficult to serve customers, and will experience a decline in service. At this time there are still many restaurants that check tables manually, by checking each table in turns. One technology that can be used to help in this situation is to use an ultrasonic sensor, this sensor can detect the presence of an object or certain objects above the sound waves of 20 kHz to 2 MHz. This can help business people to improve restaurant waiters to be better, by creating a system that can detect the arrival of customers at the restaurant table with an identifiable time and develop with various other capabilities. The research focuses on monitoring table availability by detecting the presence of customers in restaurants.